Graph Drawing
DOI: 10.1007/978-3-540-77537-9_27
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Simultaneous and Near-Simultaneous Embeddings

Abstract: Abstract.A geometric simultaneous embedding of two graphs G1 = (V1, E1) and G2 = (V2, E2) with a bijective mapping of their vertex sets γ : V1 → V2 is a pair of planar straight-line drawings Γ1 of G1 and Γ2 of G2, such that each vertex v2 = γ(v1) is mapped in Γ2 to the same point where v1 is mapped in Γ1, where v1 ∈ V1 and v2 ∈ V2.In this paper we examine several constrained versions and a relaxed version of the geometric simultaneous embedding problem. We show that if the input graphs are assumed to share no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Cabello et al [7] showed that a geometric simultaneous drawing of a matching and (a) a wheel, (b) an outerpath or, (c) a tree always exists, while there exist a planar graph and a matching that cannot be drawn simultaneously. For a quick overview of known results refer to Table 1 of [14].…”
Section: Related Work and Our Resultsmentioning
confidence: 99%
“…Cabello et al [7] showed that a geometric simultaneous drawing of a matching and (a) a wheel, (b) an outerpath or, (c) a tree always exists, while there exist a planar graph and a matching that cannot be drawn simultaneously. For a quick overview of known results refer to Table 1 of [14].…”
Section: Related Work and Our Resultsmentioning
confidence: 99%
“…A related interesting problem is to determine how many bends per edge are needed to construct a simultaneous embedding (without fixed edges) of pairs of (simple) planar graphs. The best known upper bound is two [8,9,19] and the best known lower bound is one [15]. As a final research direction, we mention the problem of constructing SEFEs of pairs of planar graphs in polynomial area, while matching our bounds for the number of bends and crossings.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, vertex v 4 has to be inside Q 3 , as otherwise edge (v 1 , v 4 ) would cross one of p 1 or p 2 . However, in this case, there is no placement for vertices v 7 and v 10 that avoids a crossing between one of edges (v 4 , v 7 ) or (v 4 , v 10 ) and one of the already drawn edges.…”
Section: Preliminariesmentioning
confidence: 99%
“…The research on this problem opened a new exciting field of problems and techniques, like ULP trees and graphs [5,7,8], colored simultaneous embedding [1], nearsimultaneous embedding [10], and matched drawings [3], deeply related to the general fundamental question of point-set embeddability.…”
Section: Introductionmentioning
confidence: 99%